2013
DOI: 10.1016/j.rmed.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Severe adenovirus pneumonia requiring extracorporeal membrane oxygenation support – Serotype 7 revisited

Abstract: The mainstay of treatment for patients with severe adenovirus pneumonia is still supportive, with the use of antivirals not apparently effective. Whilst ECMO support for rescue ventilation may be considered, the outcomes do not appear as promising as other viral pneumonias, mirroring that previously described in the paediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…Therefore, the early initiation of ECMO seems to be an intriguing option to protect the lungs of these critically ill patients (MacLaren et al 2012; Turner and Cheifetz 2013). In a case series in Low et al (2013), the duration of pre-ECMO mechanical ventilation was 2, 5, and 16 days, while in Sun et al (2014), it was 2–13 days, which were longer than in our two cases (i.e., 47 and 15 h, respectively). We also applied lung rest ventilation to the patients, as recommended by the Extracorporeal Life Support Organization (ELSO).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Therefore, the early initiation of ECMO seems to be an intriguing option to protect the lungs of these critically ill patients (MacLaren et al 2012; Turner and Cheifetz 2013). In a case series in Low et al (2013), the duration of pre-ECMO mechanical ventilation was 2, 5, and 16 days, while in Sun et al (2014), it was 2–13 days, which were longer than in our two cases (i.e., 47 and 15 h, respectively). We also applied lung rest ventilation to the patients, as recommended by the Extracorporeal Life Support Organization (ELSO).…”
Section: Discussioncontrasting
confidence: 58%
“…Sun et al (2014) described five patients with severe ARDS with confirmed HAdV-55 infection, four of whom received VV ECMO. Low et al (2013) reported three patients with confirmed HAdV-7 ARDS who were treated with VV ECMO; the reported survival rates were poor. Prodhan et al (2014) also reported that only 62 (38.0%) of 163 children with adenovirus pneumonia supported using ECMO survived.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more ARD outbreaks with severe or even fatal cases caused by HAdV-7 have been reported in Asia, especially in China, which has a large and high-density population161113151628293031. The three recent isolates circulating in Southern China (DG01; 2011), Southwestern China (CQ1198; 2010), and Northwestern China (0901HZ/ShX; 2009) were identified as a re-emergent genome type 7d (HAdV-7d) after approximately 20-year absence in China1.…”
mentioning
confidence: 99%
“…In particular, respiratory infections with human adenovirus 7 (HAdV7) have a well-documented association with severe clinical manifestations, nosocomial transmission, prolonged hospitalizations, pulmonary sequela, and deaths ( 1 6 ). Adenovirus pneumonia among immunocompetent adults is still relatively infrequent and therefore attracts considerable attention ( 4 ). …”
mentioning
confidence: 99%